Risk of adverse obstetrical and neonatal outcomes in women consuming recreational drugs during pregnancy - Sreemanjari Kandhasamy; Karine Lepigeon; Stéphanie Baggio; Roulet Céline; Michael Ceulemans; Ursula Winterfeld; Stephen P. Jenkinson; Katyuska Francini; Emeline Maisonneuve; Alice Panchaud (BMC Pregnancy and Childbirth)
Abstract Background Previously conducted studies have observed an increased risk of adverse maternal and neonatal outcomes with prenatal exposure to cocaine and opioids. However, these studies used drug-free reference groups which did not efficiently control for confounders associated with polysubstance use in pregnancy. Thus, we conducted an observational study to compare the risk of adverse obstetrical and neonatal outcomes in women who consumed cocaine and/or opioids during pregnancy to women who consumed only cannabis in pregnancy. Methods This observational study was conducted with data collected from pregnant women followed for addiction from the beginning of their pregnancy until childbirth at the perinatal consultation center Addi-Vie at CHUV Lausanne, Switzerland. Women who reported consuming cocaine, opioids, or both along with or without cannabis were included in the exposed group, while women who reported use of only cannabis during pregnancy were included in the reference group. We assessed for two adverse composite outcomes namely: adverse obstetrical composite outcome (4 outcomes) and adverse neonatal composite outcome (7 outcomes). Weighted logistic regression with weights obtained through inverse probability treatment weighting was conducted. For this analysis, we reported a conditional odds ratio (ORconditional) and 95% confidence interval (CI). Results We included 177 pregnant women in this study, with 80 included in the exposed group and 97 included in the reference group. In the exposed group, 81.2% of women reported the use of opioids, and 39.9% of women reported the use of cocaine during pregnancy. In this study, prenatal cocaine and/or opioid exposure was associated with reduced odds of adverse obstetrical composite outcomes (ORconditional: 0.39, 95% CI: 0.17–0.88) compared to prenatal cannabis use. We also observed that the pregnant women exposed to cocaine and/or opioids during pregnancy were at 3.88 (ORconditional: 3.88, 95% CI: 1.23–12.23) times higher odds of experiencing the adverse neonatal composite outcome compared to our reference group. Conclusion Prenatal use of cocaine and/or opioids during pregnancy is observed to increase the odds of adverse neonatal composite outcomes. Encouraging substance users to seek antenatal care in earlier stages of pregnancy and targeted treatment approaches through interprofessional collaboration could prevent such adverse outcomes in pregnancy.